Modern strategies for management of glycaemia in type 1 diabetes. (January 2019) - Neupane, Sankalpa; Evans, Mark L.
Abstract: The last decade has seen significant advances in the management of type 1 diabetes mellitus. The usual management of type 1 diabetes involves 'physiological' basal bolus regimens with multiple daily insulin injections. Structured education programmes are of great importance in realizing the potential of the flexible insulin regimens that are now technically possible. These offer individuals with type 1 diabetes standardized support and education in counting carbohydrates (and perhaps fat and protein) and in adjusting doses for other behavioural factors. Use of technology such as insulin pumps (continuous subcutaneous insulin infusion) and continuous glucose monitoring is growing. Increasingly, systems are becoming available that link continuous glucose monitoring to insulin pumps, thus allowing automation of at least some aspects of insulin delivery. Data from many devices – meters, pumps and continuous glucose monitors – are downloadable and can be analysed and/or shared with healthcare providers. In this chapter, we describe how modern glucose monitoring and insulin replacement can be used strategically with education to manage glucose levels in type 1 diabetes.